Development of an Aerobic Glycolysis Index for Predicting the Sorafenib Sensitivity and Prognosis of Hepatocellular Carcinoma - Pan, Yu; Hu, Geng-yuan; Jiang, Shi; Xia, Shun-jie; Maher, Hendi; Lin, Zhong-jie; Mao, Qi-jiang; Zhao, Jie; Cai, Liu-xin; Xu, Ying-hua; Xu, Jun-jie; Cai, Xiu-jun (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is a common and deadly tumor with high heterogeneity. Aerobic glycolysis is a common indicator of cancer cells and plays a key role in tumorigenesis and tumor progression. Heterogeneity in distinct metabolic pathways can be used to stratify HCC into clinically relevant subgroups, which has not been well established. In this study, we construct a model for measuring the signs of aerobic glycolysis, namely aerobic glycolysis index (AGI), by utilizing genomic data of liver hepatocellular carcinoma (LIHC) from The Cancer Genome Atlas (TCGA) project. This characteristic infers enhanced aerobic glycolysis activity in tumor tissue. AGI is associated with a poor grade of tumor differentiation and an advanced tumor stage. AGI can predict the prognosis of HCC patients in regard to both overall survival and disease-free survival. More importantly, AGI is associated with Sorafenib resistance and accurately predicts sensitivity to Sorafenib therapy. AGI might be a promising biomarker that can accurately stratify patients and improve their treatment efficacy.